BUSINESS MANAGEMENT IN CONDITIONS OF UNCERTAINTY AND CRISIS - HRABOVSKA, Іryna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the study of the features of management in conditions of uncertainty and crisis. The relevance of the study of the features of anti-crisis management decision-making with a high degree of uncertainty and risks that arise in conditions of an economic crisis is emphasized. Modern interpretations of crises and risks of the development of socio-economic systems in foreign and domestic scientific literature are considered. The main trends in the development of crises, their main features and contradictions are analyzed. The main signs of a crisis situation at the enterprise have been determined. Such features of crises as uncertainty and danger are highlighted, the essence of the concept of "uncertainty" is revealed, the development of this concept and its modern interpretation are investigated. The relationship between crisis and risk through the categories of danger and uncertainty is revealed, the existence of danger and vulnerability is justified as a necessary and sufficient condition for the occurrence and at the same time the most important characteristic of risk. Under the conditions of rapid changes in the external environment, with a significant increase in risk, attention is focused on the responsibility of the management circuit of the enterprise, which can build an optimal strategic future in difficult and unfavorable conditions with one important decision, or completely deprive the enterprise of prospects for overcoming the crisis. The importance of forming a complex of anti-crisis measures and evaluating their effectiveness in conditions of uncertainty and sharp fluctuations of the operating environment is emphasized, which is of significant practical and scientific interest. Two types of situations that create threats of different severity for the organization and require management decisions are considered: a situation of increasing number of problems and a crisis situation. The main approaches to management in conditions of crisis and uncertainty are grouped. The need to optimize the level of dangerous risk factors is emphasized, which will allow effective management decisions to be made in crisis conditions with lower resource costs and a higher probability of their implementation. Based on the analysis, approaches to assessing the economic effectiveness of anti-crisis measures are presented based on the application of quantitative and qualitative methods that allow formalizing and simultaneously processing various types of uncertainty.
Keywords: anti-crisis measures; anti-crisis management; crisis; crisis situation; uncertainty; danger; enterprise; risk; risk factors; management decisions